2001
DOI: 10.1074/jbc.c100418200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of Villin Regulates the Organization of the Actin Cytoskeleton

Abstract: We have previously shown that tyrosine phosphorylation of the actin-regulatory protein villin is accompanied by the redistribution of phosphorylated villin and a concomitant decrease in the F-actin content of intestinal epithelial cells. The temporal and spatial correlation of these two events suggested that tyrosine phosphorylation of villin may be involved in the rearrangement of the microvillar cytoskeleton. This hypothesis was investigated by analyzing the effects of tyrosine phosphorylation of villin on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 21 publications
(27 reference statements)
10
66
1
1
Order By: Relevance
“…Overlapping and Identical Actin and PIP 2 -binding Sites in Villin-Two of the PIP 2 -binding sites identified in this study correspond to actin-binding sites in villin described previously (32,35,36). PB2 has been described as the site of F-actin binding to villin prior to severing, and PB5 has been identified as the F-actin-binding site involved in the bundling function of villin.…”
Section: Conformational Changes In Pipmentioning
confidence: 99%
See 2 more Smart Citations
“…Overlapping and Identical Actin and PIP 2 -binding Sites in Villin-Two of the PIP 2 -binding sites identified in this study correspond to actin-binding sites in villin described previously (32,35,36). PB2 has been described as the site of F-actin binding to villin prior to severing, and PB5 has been identified as the F-actin-binding site involved in the bundling function of villin.…”
Section: Conformational Changes In Pipmentioning
confidence: 99%
“…Electron Microscopic Analysis of Bundling Activity of Villin-The bundling activity of villin was analyzed essentially as described before (32). The divalent cation-free actin was polymerized together with villin constructs in polymerization buffer, pH 7.0, lacking MgCl 2 .…”
Section: Pip 2 Binding Assays Cosedimentation Of Wild Type and Deletimentioning
confidence: 99%
See 1 more Smart Citation
“…Villin is tyrosine-phosphorylated both in vitro and in vivo and tyrosine phosphorylation of villin enhances its actin-severing function. 18 We have previously identified 10 phosphorylation sites in villin and demonstrated that mutation of these sites inhibits the actin severing activity of villin. 19 Further, we have demonstrated the absolute requirement of c-Src kinase for tyrosine phosphorylation of villin.…”
Section: Villin Inhibits Apoptosis By Preserving Actin Dynamicsmentioning
confidence: 99%
“…However, studies done with the villin knockout mice suggest that in the absence of villin, the actin-bundling properties associated with villin can be substituted by other proteins in the microvilli (Pinson et al, 1998); on the other hand, the actin-severing activity of the microvilli is lost (Ferrary et al, 1999). In recent years, we have demonstrated that villin's actin-modifying functions can be regulated in vitro by tyrosine phosphorylation and phosphatidylinositol bisphosphate (PIP 2 ), suggesting that villin has the potential to function as a link between receptor activation and actin cytoskeleton reorganization even in the absence of high calcium (Arora and McCulloch, 1996;Zhai et al, 2001;. In addition, we have recently demonstrated that the autoinhibited conformation of villin can be released by tyrosine phosphorylation of villin (as opposed to high Ca 2ϩ ), allowing it to sever actin at physiological Ca 2ϩ concentrations .…”
mentioning
confidence: 99%